PELATIHAN DAN PENDAMPINGAN SERTIFIKASI PROFESI TEKNISI AKUNTANSI BAGI GURU AKUNTANSI DI KOTA MALANG - Makaryanawati, Yana -; Sidharta, Eka Ananta; Harahap, Ridoni Fardeni; Furqorina, Rizka - (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2021)
The globalization of the labor market led to increased labor competition in the country. The influx of foreign workers makes domestic workers have to prepare themselves to be able to compete competitively. To win the competition, the labor must have the competency certification required by labor users. This competency certification is issued by a competent certification body. Competency certification covers various fields, including competencies in the field of accounting, which has an important role in the company as the party responsible for preparing financial statements. The need for competency information underlies the Community Service team majoring in Accounting to socialize how the mechanisms and techniques to obtain Accounting Technician competency certification. This socialization was packaged in a Webinar forum which invited 21 participants who are members of the Malang City Economics MGMP. This activity provides benefits, including providing solutions to improve the understanding and capabilities of Accounting Teachers, one of which is through training and mentoring by parties experienced in Accounting Technician Professional Certification; provide easy-to-understand training on Accounting Technician Professional Certification and provide tips and tricks for facing the Accounting Technician Competency Test; increase the motivation of the Accounting Teacher to provide training and understanding to students in preparing for the Accounting Technician Competency Test.